2013
DOI: 10.3136/fstr.19.245
|View full text |Cite
|
Sign up to set email alerts
|

Application of Probiotics from Mongolian Dairy Products to Fermented Dairy Products and Its Effects on Human Defecation

Abstract: We screened suitable lactic acid bacteria (LAB) strains for use in fermented dairy products by analyzing milk fermented with 10 probiotic LAB strains from Mongolian dairy products. Lactobacillus paracasei paracasei strain 06TCa19 was selected because of its favorable effects on pH, lactic acid production, and viable bacterial numbers after fermentation of skim milk. Then, we prepared 06TCa19 and control fermented milks and conducted a randomized, double-blind crossover study with 46 healthy women to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…(2011) suggested that lactic acid bacteria are widely distributed in natural fermented foods as indigenous microflora. Also previous studies have been performed to analyze the diversity of the microbial species existing in traditional fermented dairy products in various locations, such as Turkey ( Gurses and Erdogan, 2006 ), Africa ( Mathara et al ., 2004 ), Italy ( Losio et al ., 2014 ), Mongolia ( Takeda et al ., 2013 ), Iran ( Azadnia and Khan Nazer, 2009 ), Morocco ( Ouadghiri et al ., 200 9) etc.…”
Section: Introductionmentioning
confidence: 99%
“…(2011) suggested that lactic acid bacteria are widely distributed in natural fermented foods as indigenous microflora. Also previous studies have been performed to analyze the diversity of the microbial species existing in traditional fermented dairy products in various locations, such as Turkey ( Gurses and Erdogan, 2006 ), Africa ( Mathara et al ., 2004 ), Italy ( Losio et al ., 2014 ), Mongolia ( Takeda et al ., 2013 ), Iran ( Azadnia and Khan Nazer, 2009 ), Morocco ( Ouadghiri et al ., 200 9) etc.…”
Section: Introductionmentioning
confidence: 99%
“…DNA extraction from fecal samples and intestinal bacteria assay. For quantification by quantitative PCR, DNA was extracted from fecal samples obtained from 06cc2-treated and control mice on day 20 using an iSoFecal for Beads Beating kit (Nippon Gene) according to the manufacturer's instructions as described in a previous report (20). dna was also extracted from standard strains for each group, including Bifidobacterium longum JcM 1217 for the Bifidobacterium subspecies, the 06Tca19 strain for the Lactobacillus group, Clostridium coccoides JcM 1395 for the Clostridium group, and Bacteroides fragilis JcM 11019 for the Bacteroides-Prevotella group.…”
Section: Cell Separation Of Lpmcs By Magnetic-activated Cell Sorting mentioning
confidence: 99%
“…Bifidobacterium subspecies, C. coccoides, Bacteroides-Prevotella, and Lactobacillus groups were detected by SYBr-Green quantitative PCR. Specific primers are shown in Table II (20). Bacterial CFUs were calculated using a standard regression curve of the threshold cycle values generated from 10-fold serial dilutions of DNA samples from the standard strains with known numbers of cFus.…”
Section: Cell Separation Of Lpmcs By Magnetic-activated Cell Sorting mentioning
confidence: 99%
“…Among the isolates, Lactobacillus (L.) paracasei strain 06TCa19 improved human defecation and showed potential as a probiotic [22]. Furthermore, strain 06TCa19 demonstrated anti-H. pylori activity in vitro and in vivo [23].…”
Section: Introductionmentioning
confidence: 96%